Right where we left us : a novel - Devon, Jen, 1978- (St. Martin's Griffin, 2024)
"Temperance Jean Madigan and Duncan Brady have never gotten it right. After one radiant, secret summer together when they were eighteen, they've been on-again off-again ever since. Now, despite red-hot chemistry and TJ's closeness with Duncan's family, they're virtually strangers, only capable of adversarial banter, awkward small talk-and the occasional messy hookup. When a wedding at the Bradys' vineyard lands TJ there for the summer, their mutual avoidance strategies prove impossible. The last thing TJ wants is to be under those angsty, heated glances Duncan thinks he hides. And for Duncan, having fiery TJ constantly close is the ultimate distraction that he absolutely can't afford. When forced proximity begins to chip away at their armor, buried tensions resurface, old wounds urge confrontation, and once-in-a-lifetime love demands one last chance to finally get it right."--